Observation of ionospheric scintillation and total electron content (TEC) characteristic at equatorial / Mohd Shahrul Azree Remly - Remly, Mohd Shahrul Azree (2017)
The lonosphere is a layer of Earth's atmosphere located at 60km to reach 1000km from earth surface. The earth ionospheric layer contains free electrons that affect the propagation of radio waves.